UMKM MASYARAKAT KABUPATEN BADUNG PASCA PANDEMI COVID-19 (Jurnal Nawala Politika, 2023)
This study wants explore examine how the phenomenon of MSMEs that occurred within Badung Regency, Bali. The Indonesian economy in the third quarter of 2020 contracted by 3.5 percent, better than the previous quarter which contracted by 5.3 percent. The improvement was driven by increased government spending, especially the realization of social assistance for the National Economic Recovery Program. the research approach used is a qualitative approach. As for what is meant by qualitative research, namely research that is written to understand the phenomenon of what is experienced by the research subject as a whole, and by means of descriptions in the form of words and language, in a special natural context and by utilizing various scientific methods The surge in the number of MSMEs in Badung occurred during the Covid-19 pandemic, because the tourism sector, which has been a livelihood, is not operating. At least, nearly 75 percent of the working-age population in Badung works in the tourism sector. When the tourism sector went dormant during the pandemic, new businesses emerged. Keywords: Micro Small Medium Enterprises, Badung Regency, Covid-19